2010
DOI: 10.1111/j.1467-2979.2010.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial exploitation of global sea cucumber fisheries

Abstract: Introduction 318Methods 321Catch data sources 321Typical trajectory of sea cucumber fisheries 321Drivers of sea cucumber fisheries 322Rate of development 324Distance from Asia 324 Sensitivity analyses 325 AbstractIn recent decades, invertebrate fisheries have expanded in catch and value worldwide. One increasingly harvested group is sea cucumbers (class Holothuroidea), which are highly valued in Asia and sold as trepang or bêche-de-mer. We compiled global landings, economic data, and country-specific assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
243
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(264 citation statements)
references
References 53 publications
1
243
1
3
Order By: Relevance
“…The growing proportion of traded fishery products derived from aquaculture (FAO 2014) also raises environmental concerns (Rico et al 2012). High international demand for luxury seafood provide fishers with financial incentives to intensely target vulnerable species for live reef fish, sharks fin, fish bladders, and sea cucumbers, thereby driving the serial depletion of these largely unregulated fisheries (Cheung and Sadovy 2004;Anderson et al 2011;Sadovy de Mitcheson et al 2013), which can in turn result in serious livelihood impacts on artisanal fishers (Fabinyi and Dalabajan 2011;Christensen and Tull 2014).…”
Section: Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing proportion of traded fishery products derived from aquaculture (FAO 2014) also raises environmental concerns (Rico et al 2012). High international demand for luxury seafood provide fishers with financial incentives to intensely target vulnerable species for live reef fish, sharks fin, fish bladders, and sea cucumbers, thereby driving the serial depletion of these largely unregulated fisheries (Cheung and Sadovy 2004;Anderson et al 2011;Sadovy de Mitcheson et al 2013), which can in turn result in serious livelihood impacts on artisanal fishers (Fabinyi and Dalabajan 2011;Christensen and Tull 2014).…”
Section: Threatsmentioning
confidence: 99%
“…International regulations such as CITES 8 may be able to control trade in certain species and benefit their long-term conservation, but these are generally too slow to react to the rapid expansion of boom and bust style fisheries (Anderson et al 2011). At the national level, trade monitoring is complicated by the type and quality of data, and by undocumented trade in high-value seafood (Fabinyi et al 2014;Eriksson and Clarke 2015).…”
Section: Governance Of South China Sea Marine Fisheries Resourcesmentioning
confidence: 99%
“…Over the past few decades, the increasing international value of sea cucumber products has sparked fishery booms, often in communities where commercial sea cucumber harvesting had not previously occurred (Eriksson et al, 2015). Moreover, Anderson et al (2010) have shown that despite a trend of increasing global sea cucumber catches, the catch of individual fisheries has followed a boom-and-bust pattern, "declining nearly as quickly as they expanded" (p.1). While 'boom-bust' marine resource industries have occurred throughout history, the current speed with which markets for species of this and other echinoderms are emerging is unprecedented, supported in part by the accelerated mobility of information, technology, labour, and capital (Adger et al, 2009;Berkes et al, 2006;Eriksson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The limited research in this area reveals themes of social impacts and conflict reflective of terrestrial resource booms (Bremner and Perez, 2002;Christensen, 2011) and limited capacity for management resulting in overexploitation of stocks (Anderson et al, 2010;Eriksson et al, 2015). Rapid-onset sea cucumber fisheries thus represent an important but understudied driver of fast change in coastal communities, with heretofore-limited research into the associated social impacts and feedbacks and how these changes combine with ongoing social-ecological change.…”
Section: Introductionmentioning
confidence: 99%
“…Many fisheries have been over-exploited and many of the most valuable species have been replaced in the catch by comparatively low-value species (Anderson et al 2011). Contributing to this situation is the fact that sea cucumbers pose particular stock-assessment challenges because of their lack of hard parts for ageing, difficulty in marking them (Uthicke et al 2004) and plastic size and shape (Perry et al 1999).…”
Section: Introductionmentioning
confidence: 99%